The Influence of Profile, Connection, and Interaction Factors in the Success of Getting a Job Using Linkedin Social Media - Fifi Tirtoprodjo; Sfenrianto Sfenrianto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
A Human Resources Management (HR) survey shows that 95% of 541 HR professionals use LinkedIn to recruit passive candidates. Thus, LinkedIn users are increasingly professionalizing their profiles. However, data found that as many as 87% of people on LinkedIn use fake identities. It aims to add a connection with other companies in a way that looks professional. This study aims to determine the effect of the LinkedIn profile on individual success in getting a job because it is based on the high number of fake accounts. This study used a quantitative method, data collection was carried out in the form of a questionnaire and distributed over 20 days to 100 people. This study used a Likert scale. There are 5 Likert scale categories for answer choices: strongly disagree, disagree, neutral, agree, and strongly agree. This research model consists of 6 hypotheses, namely: The effect of profile on connection; The effect of interaction on connection; Profile influence on LinkedIn usage; the effect of interaction on LinkedIn usage; the effect of connection on LinkedIn usage; The influence of using LinkedIn on success in getting a job. The hypothesis is accepted if the T Statistics value is > 1.96. Based on calculations with the 6 hypotheses, the results are all correct except for the effect of connection on LinkedIn, for an assessment <1.96 with a total of 1,078. Then it was found that the most positive effect was in the effect of using LinkedIn on success in getting a job with a statistic of 10,159.